Knowledge and knowledge systems learning from the wonders of the mind - Geisler, Eliezer 1942- (Gale virtual reference library, 2008)
Explores the process of knowledge formation and how humans generate complex constructs from their sensorial inputs. Describes how we store and utilize this complex knowledge in organizational and technological systems that allow us to communicate, generate and manage social interactions and functions.